Management of Auricular Pseudocyst: A Comparative Study - Deepti Singh; Reema Goswami; Vivek Dudeja (International Journal of Medical Research and Review, 2014)
Introduction: Auricular pseudocyst also known as auricular seroma is an asymptomatic condition of unknown etiology affecting the pinna, commonly encountered in middle aged men. The aim of the study was to compare various modalities of treatment involved i.e. wide-bore needle aspiration and splint suturing Vs incision drainage and glove drain insertion.Materials and method: 30 patients with clinical diagnosis as auricular seroma were selected and were compared with different treatment modalities as stated and were followed for 3 months. No recurrence for at least 3 months was taken as the main outcome of treatment.Result: Ten patients out of thirty underwent wide-bore needle aspiration and splint suturing (group A) and twenty patients underwent incision drainage and glove drain insertion (group B) were followed for 3 months. None of the patients had recurrence of the disease in group B but four patients presented with recurrence in group A. Out of the two, incision and glove drain insertion was found to be successful in all cases with no recurrence.Conclusion: Incision drainage and glove drain insertion though requiring frequent visits to the hospital, was found to be more promising treatment modality in terms of recurrence.